PERANCANGAN SISTEM INFORMASI MANAJEMEN KEUANGAN UNTUK PENGENDALIAN SIMPAN PINJAM DAN LAPORAN KEUANGAN DI KOPERASI SEMARANG - Tantik Sumarlin; Ari Susanti (UNIVERSITAS STEKOM, 2020)
This research is conducted to assist the performance of cooperatives by utilizing financial management information system for savings and loan management and financial report in Cooperatives. Data collection methods used in this study is to conduct interviews on the financial and secretary of the cooperative with the object of research on the Business Cooperative